2006
DOI: 10.1111/j.1349-7006.2006.00357.x
|View full text |Cite
|
Sign up to set email alerts
|

Ki26894, a novel transforming growth factor‐β type I receptor kinase inhibitor, inhibits in vitro invasion and in vivo bone metastasis of a human breast cancer cell line

Abstract: T ransforming growth factor (TGF)-β is a multifunctional cytokine that regulates a wide range of cellular responses, including cell proliferation, differentiation, adhesion, migration, and apoptosis.(1,2) It is a potent inhibitor of various types of cells, including most epithelial cells, whereas it stimulates deposition of extracellular matrix proteins and induction of epithelialto-mesenchymal transition (EMT). TGF-β thus plays two distinct and opposing roles in cancer progression. In early stages of carcinog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
135
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 171 publications
(142 citation statements)
references
References 31 publications
5
135
0
2
Order By: Relevance
“…Stable knockdown of Smad4 expression in these cells further reinforces the importance of Smad-mediated TGF-b signaling for promoting breast cancer metastasis to bone Deckers et al, 2006). Furthermore, kinase inhibitors targeting TbRI reduce the incidence of bone metastases following left cardiac ventricle injection of MDA-MB-435 and MDA-MB-231 breast cancer cells (Bandyopadhyay et al, 2006;Ehata et al, 2007). These animal-based studies support a role for TGF-b signaling within breast tumor cells that enable aggressive metastasis to bone.…”
Section: Introductionmentioning
confidence: 53%
“…Stable knockdown of Smad4 expression in these cells further reinforces the importance of Smad-mediated TGF-b signaling for promoting breast cancer metastasis to bone Deckers et al, 2006). Furthermore, kinase inhibitors targeting TbRI reduce the incidence of bone metastases following left cardiac ventricle injection of MDA-MB-435 and MDA-MB-231 breast cancer cells (Bandyopadhyay et al, 2006;Ehata et al, 2007). These animal-based studies support a role for TGF-b signaling within breast tumor cells that enable aggressive metastasis to bone.…”
Section: Introductionmentioning
confidence: 53%
“…The MDA‐231‐D human basal‐type breast cancer cell line, a highly bone metastatic clone of MDA‐MB‐231, was described previously (Ehata et al ., 2007) and cultured in Dulbecco's modified Eagle's medium (DMEM; #11965, Thermo Fisher Scientific, Waltham, MA, USA). Hs578T human basal‐type breast cancer cells were obtained for use in this study from the American Type Culture Collection (ATCC, Manassas, VA, USA) and cultured in RPMI1640 (#11875, Thermo Fisher Scientific) with 0.01 mg·mL −1 of insulin (12585‐014, Thermo Fisher Scientific).…”
Section: Methodsmentioning
confidence: 99%
“…We found that ZEB1 directly upregulated the production of inflammatory cytokines in the basal‐type breast cancer cell lines MDA‐231‐D (a highly metastatic clone of MDA‐MB‐231; Ehata et al ., 2007) and Hs578T. ZEB2 partially showed similar function, including the induction of interleukin (IL)‐6 and IL‐8 production.…”
Section: Introductionmentioning
confidence: 98%
“…Lentivirus vectors were used to generate 2MLN-dnTbRII and control 2MLN-GFP cells as described . A human keratinocyte cells, HaCaT, and a human breast cancer cells, MDA-MB-231, were cultured as described (Ehata et al, 2007a). Human non-small-cell lung carcinoma cells, A549, human hepatocellular carcinoma cells, HuH7, and human cervical carcinoma cells, HeLa, were cultured in Dulbecco's modified Eagle's medium containing 10% fetal bovine serum, penicillin/streptomycin.…”
Section: Cell Culturementioning
confidence: 99%
“…Cell proliferation assay Cell proliferation assay was performed as described (Ehata et al, 2007a). Briefly, HaCaT and OCUM-2MLN cells were seeded in duplicate at a density of 2.5 Â 10 4 cells per well in 24-well plates.…”
Section: Chromatin Immunoprecipitationmentioning
confidence: 99%